Prophylactic transcatheter angiographic embolization reduces Forrest IIa ulcer rebleeding: A retrospective study. Issue 11 (19th March 2021) - Lan, Tian; Tong, Huan; Qian, Shuaijie; Wei, Bo; Huang, Zhiyin; Wu, Hao; Tan, Qinghua; Gao, Jinhang; Bai, Shuai; Gong, Hui; Jiang, Ting; Yang, Jinhui; et al.
Abstract : Abstract: The application of transcatheter angiographic embolization (TAE) is controversial in the treatment of ulcer bleeding. This study aims to determine rebleeding risk factors and evaluate the efficacy of prophylactic TAE (p-TAE) following endoscopic hemostasis in rebleeding prevention of Forrest lla ulcers. The medical records of Forrest lla ulcer patients who underwent endoscopic hemostasis (E group) and endoscopic hemostasis plus p-TAE (E + p-TAE group) in West China Hospital from May 2009 to May 2018 were retrospectively reviewed. Baseline characteristics, clinical efficacy, and rebleeding risk factors were analyzed. As a result, a total of 102 patients were included, with 75 and 27 patients in E and E + p-TAE group, respectively. Most of the baseline data in E and E + p-TAE group were similar except for the proportion of protruded non-bleeding visible vessel (NBVV) (E group vs E + p-TAE group, 50.7% vs 74.1%, P = .035). The rebleeding rate of E + p-TAE group (3.7%) was significantly lower than E group (24.0%) ( P = .02). The protruded NBVV (OR: 6.896, 95% confidence interval [CI]: 1.532–30.642, P = .01) and employment of p-TAE (OR: 0.038, 95% CI: 0.003–0.448, P = .009) were identified as independent risk factors for Forrest IIa ulcer rebleeding. Additionally, log-rank test indicated the rebleeding occurrence was greatly reduced by p-TAE in patients with protruded NBVVs ( P = .006). In conclusion, the protruded NBVV and employment of p-TAE were the independent risk factors tightly associated with rebleeding of Forrest IIa ulcer. P-TAE following endoscopic hemostasis could effectively prevent Forrest IIa ulcer from rebleeding.